2004
DOI: 10.1016/j.colsurfa.2004.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Breakup and strength of polystyrene latex flocs subjected to a converging flow

Abstract: Breakup of flocs (aggregates of colloidal particles) in converging flows is encountered in many industrial processes such as filtration, pipetting for sampling of flocs, and mechanical dispersion. The experiment of breakup of flocs by a converging flow opens the possibility to obtain the strength of floc against breakup. The quantity is crucial for controlling flocculator in water treatments and predicting transport of colloidal particles in aqueous environments. Therefore, the mechanism of disaggregation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 16 publications
9
35
0
Order By: Relevance
“…[8, 9, 12] and validated in Refs. [15, 16]. To find a hydrodynamically equivalent ellipsoid, we use principle components analysis (PCA) on the spatial data for centers of mass of the bacteria in the floc.…”
Section: Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8, 9, 12] and validated in Refs. [15, 16]. To find a hydrodynamically equivalent ellipsoid, we use principle components analysis (PCA) on the spatial data for centers of mass of the bacteria in the floc.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Direct observation of the fragmentation process is challenging, though it has been visualized for flocs in extensional [811] swirling and contraction [12] flows. Various strategies have also been proposed to infer floc strength indirectly including microscale cantilever beams [13], atomic force microscopy [14], and traditional particle sizer techniques [15, 16] (augmented by modeling).…”
Section: Introductionmentioning
confidence: 99%
“…Computer software is required for the image processing and analysis and a variety of commercial products are available. Image analysis is often combined with microscopy by mounting a CCD camera onto the microscope (Li and Ganczarczyk, 1986;Cousin and Ganczarczyk, 1998;da Motta et al, 2001;Kobayashi, 2004). The advent of photography and image analysis has allowed much quicker measurements of an almost inexhaustible number of different floc size measurements to be made from floc samples when compared to traditional microscope methods (Wang and Gregory, 2002).…”
Section: Photography and Image Analysismentioning
confidence: 99%
“…This relationship was later supported by simulation work of Higashitani and Imura (1998). Several authors have observed the break up of floes when flowing through sudden restrietions or other types of eonverging flows (Blaser 2000a(Blaser , 2000bJames et al, 2003;Kobayashi, 2004,). Patil and Pandit (2007) estimated that the energy dissipated per kg of solids disrupted was four orders of magnitude lower for hydrodynamic treatment as compared to ultrasound for the creation of nano-suspensions.…”
Section: £=•mentioning
confidence: 85%
“…Previous work in this area either focused on very high pressures (He, 2009), focused on very small scales, or did not address the complex floe structure unique to secondary wastewater effluents (Blaser 2000a(Blaser , 2000bJames et al, 2003;Kao and Mason, 1975;Kobayashi, 2004). This study addresses the mechanism of secondary effluent floe disruption, under conditions of relatively low pressure using a bench-scale apparatus.…”
Section: £=•mentioning
confidence: 99%